2015
DOI: 10.1007/s11999-014-4047-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Deltoid Size and Fatty Infiltration of the Deltoid and Rotator Cuff Correlate to Outcomes After Reverse Total Shoulder Arthroplasty

Abstract: Background Reverse total shoulder arthroplasty (RTSA) allows the deltoid to substitute for the nonfunctioning rotator cuff. To date, it is unknown whether preoperative deltoid and rotator cuff parameters correlate with clinical outcomes. Questions/purposes We asked whether associations exist between 2-year postoperative results (ROM, strength, and outcomes scores) and preoperative (1) deltoid size; (2) fatty infiltration of the deltoid; and/or (3) fatty infiltration of the rotator cuff.Methods A prospective RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…This is important, as both preoperative and postoperative atrophy or fatty infiltration of the deltoid have been correlated with functional outcome scores after RTSA. 6,27 Lower functional scores in patients with prior RCR might also be due to postoperative scarring or even psychological factors related to having a failed procedure and requiring another surgery with another prolonged rehabilitation period. Unfortunately, the main clinical dilemma of how to treat an elderly patient with a large RCT and no or minimal glenohumeral arthritis remains unresolved based on the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as both preoperative and postoperative atrophy or fatty infiltration of the deltoid have been correlated with functional outcome scores after RTSA. 6,27 Lower functional scores in patients with prior RCR might also be due to postoperative scarring or even psychological factors related to having a failed procedure and requiring another surgery with another prolonged rehabilitation period. Unfortunately, the main clinical dilemma of how to treat an elderly patient with a large RCT and no or minimal glenohumeral arthritis remains unresolved based on the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic studies have highlighted the importance of the infraspinatus as an external rotator, and recent studies have demonstrated the importance of the teres minor in reverse shoulder arthroplasty and latissimus transfers [2,6]. The current paper demonstrates an excellent step forward in improving our knowledge of the external rotators of the shoulder by determining the key physical exam maneuvers to detect a functional teres minor.…”
mentioning
confidence: 83%
“…It is also important to utilize imaging modalities carefully to assess for teres minor size and fatty infiltration, as well as the size and function of the deltoid. Wiater et al [6] suggest that posterior deltoid size and muscle quality as assessed by fatty infiltration are important factors associated with patient-reported outcomes and range of motion after reverse shoulder arthroplasty. Studies such as these that quantify the amount of fatty infiltration, rather than qualitatively score the amount of fat, demonstrate the next step forward in preoperative imaging to help us guide our patients' expectations after surgery.…”
mentioning
confidence: 99%
“…Besides range of motion, strength plays an important role in ADL. Wiater et al showed that the preoperative deltoid size and fatty infiltration correlates with postoperative functional scores and strength [52]. In terms of rehabilitation, this means that a reduction in postoperative deltoid atrophy could lead to improved function, but irreversible fatty infiltration of the deltoid may only allow functional improvement to a certain limit.…”
Section: Summary Of Rehabilitation Protocols In Clinical Studiesmentioning
confidence: 99%